Impasses e possibilidades do pensamento decolonial no ensino superior: o caso de uma universidade colombiana - Cruz, Denise Gonçalves da (2019)
This master's research identify aspects that underpin the Biology Degree racial debate. "Francisco José de Caldas District University" is located in Bogota, Colombia. The investigation, called "Knowledge, research and curricular innovations in teacher education for ethnic-racial diversity in higher education: questions and contributions of ethnic-racial and cultural matrices, African and Afro-descendant knowledge" its linked to the Academic Development Program Abdias Nascimento, subsidized by the Coordination of Improvement of Higher Education Personnel (CAPES) in Brazil during the year 2018. the research was developed from analyzes of documents and interviews with the students aiming to identify if and to what extent,the university included in its curriculum of formation the contents referring to ethnic-racial diversity and, if so, these inclusions modified the formation offered.This data was producted by qualitative approach and using tools outlined by the methodology of Case Studies. The results allowed us to find elements to new discussions, and make it possible to rethink the degree in biology from a decolonial perspective. The investigations construction that intersect the relationship between biology and racial relations not only in Colombia but also in Latin America.